The influence of supplier information sharing and information quality on strategic partnerships and internal lean practices among small to medium enterprises in South Africa - Sikhwari, Tina Mesmer (My University, 2015)
The focus of this study was to examine the relationship between information sharing, information quality, strategic partnership and internal lean practices among Small and Medium-sized Enterprises in South Africa. It is essential to understand practitioners’ and entrepreneurs’ current knowledge towards the topic at hand in order to determine what interventions would be most beneficial in helping to curb the problem of the lack of knowledge in this area and to understand the underlying causes behind the problem, while creating awareness and giving new insight to those who are already aware of this topic. Data was collected from a sample of 350 Small to Medium Enterprises and the measurement items in the measuring instrument were measured using a 5-point likert scale. Thereafter the collected data was coded and analysed by means of structural equation modelling using the AMOS 21 software package. The results indicate that supplier information sharing and information quality have a strong influence on strategic partnership and in turn strategic partnership has a strong influence on internal lean practices among Small to Medium Enterprises. This indicates that the level and quality of information shared between Small to Medium Enterprises and their suppliers has a positive effect on the strength of their partnerships as well as on the internal practices of each Small to Medium Enterprise. Based on these results, conclusions were drawn and recommendations were put forward on how internal lean practices in Small to Medium Enterprises can be improved by means of information sharing, information quality and strategic partnerships.
Tech. (Logistics, Faculty of Management Sciences), Vaal University of Technology
Keywords: Supplier information sharing; Information quality; Strategic partnership; Internal practices; 658.5; Lean manufacturing; Strategic alliances (Businesses)